1992
DOI: 10.1139/x92-104
|View full text |Cite
|
Sign up to set email alerts
|

Shoot-tip respiration of 1st-year interior and coastal Douglas-fir seedlings during bud development

Abstract: Respiration rates of shoot tips of 1st year (1-0) Douglas-fir (Pseudotsugamenziesii (Mirb.) Franco) seedlings of one interior and one coastal seed lot were measured using a polarographic Clark-type oxygen probe. Total respiration of shoot tips was high in August and early September (32 nmol O2•mg−1•h−1), the period of most rapid bud development, decreased to between 8 and 16 nmol O2•mg−1•h−1 in the later stage of bud development, and was between 8 and 12 nmol O2•mg−1•h−1 when bud development was complete. Bud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Thus, the present results are consistent with studies of seeds (Bewley and Black 1994), but not with results obtained with vegetative Populus balsamifera buds (Bachelard and Wightman 1973) in which respiration increased during the latter part of dormancy release from February onwards. Fielder and Owens (1992) reported similar results and suggested that dormancy could be used to assess bud dormancy status in Douglas-fir (Pseudotsuga menziezii) buds. However, they defined dormancy as suspension of mitotic divisions in the apex (cf.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Thus, the present results are consistent with studies of seeds (Bewley and Black 1994), but not with results obtained with vegetative Populus balsamifera buds (Bachelard and Wightman 1973) in which respiration increased during the latter part of dormancy release from February onwards. Fielder and Owens (1992) reported similar results and suggested that dormancy could be used to assess bud dormancy status in Douglas-fir (Pseudotsuga menziezii) buds. However, they defined dormancy as suspension of mitotic divisions in the apex (cf.…”
Section: Discussionmentioning
confidence: 66%
“…In accordance with the seasonal growth pattern of northern trees the respiratory rate of vegetative buds decreases in the autumn and increases in the spring. This is demonstrated both in conifers (Kozlowski and Gentile 1958;Fielder and Owens 1992) and hardwood species (Pollock 1953(Pollock , 1960Bachelard and Wightman 1973). Temperature is the most important external factor for respiration, and even though the level is relatively low during dormancy when growth is arrested, appreciable amounts of carbohydrates are consumed in maintenance during warm periods (Tranquillini 1979;Paembonan et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is supported by the fact that most plant mitochondria contain a cyanide and antimycin‐insensitive alternative terminal oxidase (Lambers, 1980; Moreau & Romani, 1982). The alternative respiratory pathway has been detected in different tissues of many plants belonging to different taxa, for example ripening fruits (Cruzhernandez & Gomezlim, 1995), roots and cotyledons of soybean, potato, sweet potato and cassava (Day et al ., 1994; Millar et al ., 1994; Ribascarbo et al ., 1995), sugar beet callus (Shugaev et al ., 1998), Acer pseudoplatanus (Aubert et al ., 1997), rootstocks of pears (Wagner et al ., 1992; Tamura et al ., 1996), nongreen tissues of Petunia hybrida (Wagner & Wagner, 1995), water‐stressed plants of sorghum (Kumar & Sinha, 1994), shoot tips of Douglas fir (Fielder & Owens, 1992), roots of white spruce (Weger & Guy, 1991), Convolvulus (Van der Plas et al ., 1977), wheat (Lundegårdh, 2001) and beans (Rychter et al ., 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The heat supply required to raise the tissue temperature of the central column of a female flower several degrees above ambient temperature was calculated using two different approaches. (1) The method described by van Gardingen & Grace (1991); in this method, the heat transfer is modelled as a combination of forced and free convection, assuming no transpirational cooling. (2) An exact method using computational fluid dynamics; heat and CO 2 transfer in this method is solved using a commercial software package FLUENT (Kim et al ., 1997).…”
Section: Heat Balance Modelsmentioning
confidence: 99%